Preparation and application of Anderson type polyacid modified MXene composite material

By synthesizing the Como6-TRIS@MXC composite catalyst under heating conditions, the Como6-Tris is evenly attached to the surface of the MXENE nanometer, solving the problem of poor electrical catalytic capacity and MXENE oxidation of polyphromic acid-based materials, and increased the ammonia-producing catalysts. Electric catalytic efficiency.

CN119368214APending Publication Date: 2025-01-28HARBIN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411425621.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-13
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

Poor electrocatalytic capacity, easy dissolution, and easy oxidation of MXene as a substrate material due to polyacid enrichment affects the electrocatalytic efficiency of ammonia-generating catalysts.

Method used

By the functionalized COMO6 and carboxyl-based MXENE, the Como6-Tris@MXC composite catalyst is synthesized under heating conditions, and the Como6-Tris is evenly attached to the surface of the MXENE nanometer to form a nanocrite-like composite catalytic material.

Benefits of technology

It improves the composite material ratio and electronic transmission capacity, enhance the efficiency of electrical catalytic nitrate root restoration of ammonia, and alleviate the problem of dissolving and MXENE oxidation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005082094460000011
    Figure HDA0005082094460000011
  • Figure HDA0005082094460000012
    Figure HDA0005082094460000012
  • Figure HDA0005082094460000021
    Figure HDA0005082094460000021
Patent Text Reader

Abstract

The invention relates to a preparation method and an application of an Anderson type polyacid modified MXene composite material. The invention aims to solve the problems that the existing polyacid-based material is poor in electro-catalysis capability and easy to dissolve due to polyacid enrichment, MXene is easy to oxidize as a substrate material and the like, and the electro-catalysis efficiency of the ammonia production material is improved. The preparation method comprises the following steps: firstly, carrying out carboxyl functionalization on MXene to form MXene-COOH (MXC for short); meanwhile, carrying out amino functionalization on Anderson type cobalt molybdenum polyacid (NH4) 3 [CoMo6O24H6] (abbreviated as CoMo6) by adopting tris (hydroxymethyl) aminomethane (Tris for short), so as to form CoMo6-Tris; further, the MXC and the CoMo6-Tris are subjected to amido bond generation under the heating condition, and the CoMo6-Tris (at) MXC composite material is obtained. According to the preparation method disclosed by the invention, CoMo6-Tris type polyacid grows on the surface of MXC in a bonding manner in a heating and stirring manner, and the CoMo6-Tris-coated MXC nanosheet composite electrocatalyst is prepared. The method solves the problems that CoMo6 polyacid is easy to dissolve and agglomerate in the catalysis process, MXene is easy to oxidize in the catalysis process and the like. The CoMo6-Tris-coated MXC composite electro-catalytic material obtained by the invention is used for producing ammonia by electro-catalyzing nitrate radical reduction at normal temperature and normal pressure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the preparation and application of an Anderson-type polyacid-modified MXene composite material. Background Art

[0002] Polyoxometalates (POMs), also known as polyacids, are nano-sized electron-rich inorganic metal oxygen-containing clusters composed of pre-transition metals (Mo, W, V, Nb, Ta) coordinated with oxygen atoms. Polyacids have rich structures and diverse compositions. Their composition, structure and charge density can be adjusted by changing the types of heteroatoms. However, during the synthesis process, polyacids are highly soluble in water and organic solvents, which makes them less stable as electrode materials. Anderson-type POMs are often selected as the best organic covalently modified materials because of their stable structure and easy modification. By reacting Anderson-type POMs with tris(hydroxymethyl)aminomethane (Tris for short), the organic ligand Tris can be successfully covalently modified on both sides of the bilateral Anderson-type POM, which is convenient for constructing polyacid-based composite materials with specific functions.

[0003] Two-dimensional transition metal carbides and / or nitrides, also known as MXene, have attracted widespread attention due to their unique morphology and metal-like conductivity. They have application prospects in electrocatalysts, optical sensors, electronics, biomedicine, electromagnetics, and energy storage devices. However, due to the presence of hydroxyl groups (-OH) on the surface, the most common problem of MXene is surface oxidation, which leads to performance degradation. Modification of the surface carboxyl groups of MXene by chloroacetic acid and sodium hydroxide can solve the above problems, making MXene a potential electrocatalytic material even in open-air and humid environmental systems. At the same time, the MXene modified with carboxyl groups is easier to form a composite material with amino-functionalized Anderson-type POMs to solve the problem that polyacids are easily soluble in water and easy to agglomerate when used alone. Summary of the invention

[0004] The purpose of the present invention is to solve the problems of poor electrocatalytic ability and easy solubility of polyacid-based materials due to polyacid enrichment and easy oxidation of MXene as a substrate material, and to improve the electrocatalytic efficiency of ammonia production catalysts.

[0005] The present invention provides a method for functionalizing Tris with (NH4)3[CoMo6O 24H6] (abbreviated as CoMo6), namely CoMo6-Tris, and MXC formed by carboxyl functionalized MXene, are synthesized by heating to form a composite catalyst for electrocatalytic nitric acid reduction and synthesis of ammonia. The present invention relates to the preparation and application of a CoMo6-Tris@MXC composite catalyst, and obtains a two-dimensional nanosheet composite electrocatalytic material in which CoMo6-Tris is uniformly attached to the surface of carboxyl functionalized MXene, and its expression is CoMo6-Tris@MXC.

[0006] The synthesis of CoMo6-Tris@MXC composites was completed in the following steps:

[0007] 1. Preparation of CoMo6-Tris polyacid: [N(C4H9)4]4[α-Mo8O 26 ](8g), cobalt acetate (1.4-1.8g), (HOCH2)3CNH2 (Tris, 1.56-1.86g) were dissolved in 20mL acetonitrile and condensed and refluxed at 80-90°C for 16-24 hours; after the reaction reflux was completed, the solution was cooled to room temperature, and the solution was filtered to remove the lavender solid; the filtered liquid was exposed to ether vapor for 2-3.5h to produce a white precipitate, which was filtered; the solution was then placed in ether vapor for 3-5 days to produce a precipitate, the precipitate was filtered and washed with acetonitrile and ether, and then vacuum dried to obtain a purple powder, thereby obtaining CoMo6-Tris;

[0008] 2. Preparation of carboxyl-functionalized MXene: Ultrasonicate 100-150 mg of flaky MXene powder to fully disperse it in 200-250 mL of deionized water. Then, add 2.8-4.2 g of chloroacetic acid and 1.8-2.7 g of sodium hydroxide to the above solution and fully disperse it. Subsequently, inject a large amount of high-purity nitrogen into the mixture solution to avoid oxidation. The above solution is continuously stirred at not less than 60°C for 24-36 hours, and then centrifuged and washed several times with a large amount of deionized water until the pH is close to 7. Finally, freeze-drying to obtain carboxyl-functionalized MXene flake powder (abbreviated as: MXC);

[0009] 3. Preparation of composite materials: Add 20-35 mg MXC to 40-60 mL acetonitrile, ultrasonicate until completely dispersed, then introduce nitrogen to avoid oxidation, add 0.5-0.8 mL triethylamine and continue to introduce nitrogen for 30-50 minutes, add 0.2-0.35 g CoMo6-Tris polyacid to 20-30 mL acetonitrile and stir for a while to dissolve it, mix the two solutions and transfer them to a 250 mL round-bottom flask, heat at not less than 60°C for 24-36 hours, and continuously introduce nitrogen into the interior during the heating process. After the round-bottom flask cools down, centrifuge the sample and wash it. Vacuum dry for 3-5 days. Obtain CoMo6-Tris@MXC.

[0010] The acetonitrile in step 1 is 60-80 mL of acetonitrile at a temperature range of not less than 80°C.

[0011] The volume of the deionized water in step 2 is 200-250 mL.

[0012] The masses of chloroacetic acid and NaOH described in step 2 are 2.8-4.2 g and 1.8-2.7 g respectively.

[0013] The volume of acetonitrile described in step 3 is 60-90 mL.

[0014] The heating described in step 3 has a heating temperature of not less than 60° C. and a heating time of 1440 to 1450 minutes.

[0015] The heating process described in step 3 should be carried out under the condition of continuous nitrogen flow.

[0016] Compared with the prior art, the present invention has the following characteristics:

[0017] 1. The present invention is the first to prepare a CoMo6-Tris@MXC composite electrocatalyst by heating synthesis. The CoMo6-Tris@MXC composite electrocatalyst is in the form of nanosheets. The nanostructure formed by the cross-sheets increases the specific surface area of ​​the material. The composite of MXC nanoflowers and CoMo6-Tris enhances the electron transport capacity of the catalyst. The CoMo6-Tris polyacid is uniformly attached to the surface of the MXC nanosheet layer, increasing the specific surface area of ​​the composite material and improving the electrocatalytic capacity.

[0018] Second, the present invention uses heating synthesis to make CoMo6-Tris polyacid uniformly dispersed and stably attached to the surface of MXene nanosheets. This alleviates the problem of CoMo6-Tris polyacid being easy to dissolve and agglomerate during the catalytic reaction. The present invention is the first example of CoMo6-Tris@MXC polyacid composite electrocatalytic material being applied to electrocatalytic nitrate reduction to produce ammonia. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a scanning electron microscope image of MXene material.

[0020] Figure 2 This is a scanning electron microscope image of MXC material.

[0021] Figure 3 This is a scanning electron microscope image of CoMo6-Tris@MXC composite material.

[0022] Figure 4 This is the transmission electron microscopy image of CoMo6-Tris@MXC composite material.

[0023] Figure 5 Infrared spectra of MXene, CoMo6-Tris@MXC and CoMo6-Tris composites.

[0024] Figure 6 XRD patterns of MXene, CoMo6-Tris@MXC and CoMo6-Tris composites.

[0025] Figure 7 This is a graph of the ammonia production rate of CoMo6 and CoMo6-Tris@MXC composites in a neutral system (0.1 mol / L NaNO3 and 0.1 mol / L Na2SO4) and a voltage of -0.8 to -1.2 V for one hour at room temperature and pressure.

[0026] Figure 8 This is the electrochemical linear sweep voltammetry (LSV) diagram of CoMo6-Tris@MXC composite material in the presence or absence of nitrate. DETAILED DESCRIPTION

[0027] The present invention is further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.

[0028] Implementation Case 1

[0029] This embodiment is a preparation case of nanosheet carboxylated MXene, which is prepared according to the following method:

[0030] 100 mg of flaky MXene powder was ultrasonically treated to be fully dispersed in 200 mL of deionized water. Then, 2.8 g of chloroacetic acid (ClCH2COOH) and 1.8 g of sodium hydroxide (NaOH) were added to the above solution and fully dispersed. Subsequently, a large amount of high-purity nitrogen was injected into the mixture solution to avoid oxidation. The above solution was stirred continuously at 60 ° C for 24 hours, and then centrifuged and washed several times with a large amount of deionized water until the pH was close to 7. Finally, the carboxyl-functionalized MXene flake powder was obtained after freeze drying.

[0031] Implementation Case 2

[0032] This embodiment provides a CoMo6-Tris@MXC nanosheet catalyst, which is prepared according to the following method:

[0033] (1) Preparation of CoMo6-Tris polyacid: [N(C4H9)4]4[α-Mo8O 26](8g), cobalt acetate (1.4g), (HOCH2)3CNH2 (Tris, 1.56g) were dissolved in 20mL acetonitrile and condensed and refluxed at 80℃ for 16 hours; after the reaction reflux was completed, the solution was cooled to room temperature, and the solution was filtered to remove the lavender solid; the filtered liquid was exposed to ether vapor for 2h to produce a white precipitate after filtration; the solution was then placed in ether vapor for 3 days to produce a precipitate, the precipitate was filtered and washed with acetonitrile and ether, and then vacuum dried to obtain a purple powder, thereby obtaining CoMo6-Tris.

[0034] (2) Preparation of composite materials: Add 20 mg MXC to 40 mL acetonitrile, sonicate until completely dispersed, then introduce nitrogen to avoid oxidation, add 0.5 mL triethylamine and continue introducing nitrogen for 30 minutes, add 0.2 g CoMo6-Tris polyacid to 20 mL acetonitrile and stir for a while to dissolve it, mix the two solutions and transfer them to a 250 mL round-bottom flask, heat at 60 ° C for 24 hours, and continuously introduce nitrogen during the heating process. After the round-bottom flask is cooled, the sample is centrifuged and washed. Vacuum dry for 3 days. CoMo6-Tris@MXC is obtained.

[0035] Comparative Case 1

[0036] This comparative case provides a carboxyl-functionalized MXene nanosheet, which is different from Example 2 in that: (2) Preparation of MXC material: 100 mg of flaky MXene powder was ultrasonically treated to fully disperse in 200 mL of deionized water. Then, 2.8 g of chloroacetic acid (ClCH2COOH) and 1.8 g of sodium hydroxide (NaOH) were added to the above solution and fully dispersed. Subsequently, a large amount of high-purity nitrogen was injected into the mixture solution to avoid oxidation. The above solution was stirred continuously at 60 ° C for 24 hours, and then centrifuged and washed several times with a large amount of deionized water until the pH was close to 7. Finally, the carboxyl-functionalized MXene sheet powder was obtained after freeze drying.

[0037] Comparative Case 2

[0038] This comparative case provides a CoMo6-Tris@MXC nanosheet catalyst, which is different from Example 2 in that: (2) Preparation of composite material: MXC is dispersed in 60 mL of acetonitrile solution, and then nitrogen is introduced for 30 minutes to avoid oxidation, and triethylamine (0.5 mL) is added, stirred for 0.5 hours to fully dissolve the first two raw materials, and 0.2 g of CoMo6-Tris is added. Heat at 60°C for 24 hours, and nitrogen is continuously introduced during the heating process. This comparative case can obtain a CoMo6-Tris@MXC composite material.

[0039] The present invention will be further described below in conjunction with the accompanying drawings and embodiments:

[0040] Figure 1 The figure shows a scanning electron microscope image of the MXene material. It is observed that the MXene material is micron-sized, and multiple nanosheets are interspersed and stacked to form a nanosheet structure.

[0041] Figure 2 The figure shows the scanning electron micrograph of the MXC composite material. It is observed that the surface of the nanosheet-like MXene is rough, indicating that the surface of the MXene nanosheet is successfully carboxylated.

[0042] Figure 3 Shown is a scanning electron microscope image of the CoMo6-Tris@MXC material, in which a nanoparticle structure with surface protrusions is observed to be accumulated on the lamellar structure.

[0043] Figure 4 The following is a transmission electron micrograph of the CoMo6-Tris@MXC composite material. A rough surface is observed.

[0044] Figure 5 The infrared spectra of MXene, CoMo6-Tris@MXC and CoMo6-Tris composite materials are shown in the figure. As shown in the figure, the material has a wavelength of 700-1400 cm -1 There are infrared characteristic peaks in the range, and the infrared characteristic peaks of CoMo6-Tris in this range are obvious. The composite material CoMo6-Tris@MXC contains obvious infrared characteristic peaks of CoMo6-Tris.

[0045] Figure 6 Shown are the XRD patterns of MXene, CoMo6-Tris@MXC and CoMo6-Tris composites. Comparing MXene and CoMo6-Tris, the CoMo6-Tris@MXC prepared by heating and stirring has higher purity, and the CoMo6-Tris@MXC composite also has obvious characteristic peaks of CoMo6-Tris.

[0046] Figure 7 The graphs show the ammonia production rate of CoMo6-Tris and CoMo6-Tris@MXC composites in a neutral system (0.1 mol / L NaNO3 and 0.1 mol / L Na2SO4) at room temperature and pressure and a voltage of -0.8 to -1.2 V for 1 hour. The average ammonia production efficiency of CoMo6-Tris@MXC composite is 4.99 mg h -1 mg cat. -1, much higher than CoMo6 monomer and other composite materials, CoMo6-Tris@MXC has good electrocatalytic nitrate reduction to ammonia activity. Therefore, the introduction of CoMo6-Tris in the present invention improves the electrocatalytic efficiency of MXC, and the CoMo6-Tris@MXC composite material can be used as an efficient electrocatalytic nitrate reduction catalyst.

[0047] Figure 8 The electrochemical linear sweep voltammetry (LSV) graph of the CoMo6-Tris@MXC composite material in the presence or absence of nitrate is shown. As shown in the figure, the CoMo6-Tris@MXC composite material has stronger catalytic ability and better catalytic potential.

[0048] In summary, the preparation and application of an Anderson-type polyacid-modified MXene composite material synthesized by the present invention, the addition of CoMo6 enhances the efficiency of the electrocatalytic nitrate reduction to produce ammonia of the flaky material, increases the specific surface area of ​​the material, enhances the electrocatalytic ability, and has good potential in the electrocatalytic nitrate reduction to produce ammonia.

Claims

1. A preparation process of an Anderson-type polyacid-modified MXene composite material, characterized in that: (1) Preparation of CoMo6-Tris polyacid: [N(C4H9)4]4[α-Mo8O 26 ](8g), cobalt acetate (1.4g), (HOCH2)3CNH2 (Tris, 1.56g) were dissolved in 20mL acetonitrile and condensed and refluxed at 80℃ for 16 hours; after the reaction reflux, the solution was cooled to room temperature and filtered to remove the lavender solid; the filtered liquid was exposed to ether vapor for 2h and a white precipitate appeared after filtration; The solution was then placed in ether vapor for 3 days to produce a precipitate, which was filtered and washed with acetonitrile and ether and then vacuum dried to obtain a purple powder, thereby obtaining CoMo6-Tris; (2) Preparation of carboxyl-functionalized MXene: 100 mg of flaky MXene powder was ultrasonically treated to fully disperse in 200 mL of deionized water. Then, 2.8 g of chloroacetic acid (ClCH2COOH) and 1.8 g of sodium hydroxide (NaOH) were added to the above solution and fully dispersed. Subsequently, a large amount of high-purity nitrogen was injected into the mixture solution to avoid oxidation. The above solution was continuously stirred at 60 °C for 24 hours, and then centrifuged and washed several times with a large amount of deionized water until the pH was close to 7. Finally, the carboxyl-functionalized MXene flake powder was obtained after freeze drying; (3) Preparation of composite materials: 20 mg MXC was added to 40 mL acetonitrile, and the mixture was ultrasonically dispersed. Then nitrogen was introduced to avoid oxidation. After 0.5 mL triethylamine was added, nitrogen was introduced for 30 minutes. 0.2 g CoMo6-Tris polyacid was added to 20 mL acetonitrile and stirred for a period of time to dissolve it. The two solutions were mixed and transferred to a 250 mL round-bottom flask, sealed and heated at 60°C for 24 hours. After the round-bottom flask was cooled, the sample was centrifuged, washed, and vacuum dried for 3 days to obtain CoMo6-Tris@MXC.

2. The [N(C4H9)4]4[α-Mo8O 26 ](8g), cobalt acetate (1.4g), (HOCH2)3CNH2(Tris,1.56g).

3. According to claim 1, the acetonitrile described in step (1) is 20mL acetonitrile in a temperature range of 70 to 75°C.

4. The volume of the deionized water according to step (2) of claim 1 is 200-210 mL; 2.8 g of chloroacetic acid (ClCH2COOH) and 1.8 g of sodium hydroxide (NaOH).

5. According to the heating in step (2) of claim 1, the heating temperature is 60-65° C. and the heating time is 1440-1450 minutes.

6. 20 mg of MXC and 200 mg of CoMo6-Tris according to step (3) of claim 1.

7. After the mixture is uniformly dispersed according to step (3) of claim 1, 0.5 mL of triethylamine is added and nitrogen is continuously introduced for 30 to 50 minutes.

8. The volume of acetonitrile according to step (3) of claim 1 is 80-85 mL.

9. According to the heating in step (3) of claim 1, the heating temperature is 60-65° C. and the heating time is 1440-1450 minutes.